Empathy in Toddlers: The Role of Emotion Regulation, Language Ability, and Maternal Emotion Socialization Style - Ornaghi, Veronica; Conte, Elisabetta; Grazzani, Ilaria (Frontiers in Psychology, 2020)
We investigated, through a cross-sectional study, whether and to what extent toddlers’ empathy is associated with a set of individual and family factors known to foster positive social skills in early childhood: children’s own emotion regulation, language ability, and maternal emotion socialization style. Participants were 320 toddlers (Mage=28.8 months; SD=3.55) and their mothers. The children came from middle-SES families and were recruited at 34 infant-toddler centers. We used parent-report measures to assess the toddlers’ competences and a self-report questionnaire to evaluate maternal emotion socialization style (coaching vs dismissing). Toddlers’ empathic responses, as reported by their mothers, were positively and significantly correlated respectively with their positive emotion regulation, language skills, and maternal emotion-coaching style. Stepwise regression analysis revealed that emotion regulation and maternal emotion-coaching style contributed to explaining variance in toddlers’ empathy, after controlling for the effects of children’s age and language ability. Moderation analysis showed that emotion regulation skills did not moderate the relationship between maternal emotion-coaching style and children’s empathy. We discuss the implications of these findings.